ANALISIS POTENSI SEKTOR PERTANIAN DALAM MENYERAP TENAGA KERJA DI KABUPATEN TEMANGGUNG TAHUN 2012 – 2016 - Miftakudin .; Whinarko Juliprijanto; Panji Kusuma Prasetyanto (Universitas Tidar, 2019)
The purpose of this study is to find out whether the agricultural sector as a base sector in absorbing labor, knowing the growth of agricultural sector activities in absorbing labor, knowing the agricultural sector in absorbing labor in Temanggung Regency. The research method used is the Location Quotient data analysis method, Growth Ratio Model, Shift Share, and Overlay. The data used are data on the agricultural sector of Central Java and Temanggung Regency 2012-2016. The results of this study indicate that the agricultural sector in Temanggung Regency in absorbing labor is not a base sector, with an LQ value <1. The MRP calculation results show that the agricultural sector in the reference area (Central Java Province) has rapid growth, while in the study area (Temanggung Regency) The agricultural sector has a slow growth in absorbing labor. Based on Overlay criteria the agricultural sector is a sector that is not potential both in terms of growth and in terms of contribution criteria, but in the Shift-share results shows that the magnitude of the economic performance, labor in the agricultural sector during 2012-2016 increased by 10.627 people.